Perturbing π‐clouds with Substituents to Study the Effects on Reaction Dynamics of gauche‐1, 3‐Butadiene to Bicyclobutane Electrocyclization. Issue 3 (22nd November 2022) - Kalita, Papu; Medhi, Biman; Singh, Haobam Kisan; Bhattacharyya, Himangshu Pratim; Gupt, Nikhil; Sarma, Manabendra
Abstract: The conical intersection (CI) governs the ultra‐fast relaxation of excited states in a radiationless manner and are observed mainly in photochemical processes. In the current work, we investigated the effects of substituents on the reaction dynamics for the conversion of gauche ‐1, 3‐butadiene to bicyclobutane via photochemical electrocyclization. We incorporated both electron withdrawing (−F) and donating (−CH3 ) groups in the conjugated system. In our study, we optimized the minimum energy conical intersection (MECI) geometries using the multi‐configurational state‐averaged CASSCF approach, whereas, to study the ground state reaction pathways for the substituted derivatives, dispersion corrected, B3LYP‐D3 functional was used. The non‐adiabatic surface hopping molecular dynamics simulations were performed to observe the behaviour of electronic states involved throughout the photoconversion process. The results obtained from the multi‐reference second‐order perturbation correction of energy at the XMS‐CASPT2 level of theory, topography analysis, and non‐adiabatic dynamics suggest that the −CH3 substituted derivatives can undergo faster thermal conversion to the product in the ground state with a smaller activation energy barrier compared to −F substituted derivative. Our study also reveals that the GBUT to BIBUT conversion follows both conrotatory and disrotatory pathways, whereas, on substitution with −F or −CH3, the conversion proceeds via the conrotatory pathway. Abstract : The electrocyclization of gauche ‐1, 3‐Butadiene (GBUT) to Bicyclobutane (BIBUT) and its substituted −F and −CH3 derivatives were studied. The GBUT/F‐GBUT to BIBUT/F‐BIBUT photoconversion can occur via a conical intersection (CI) geometry, whereas the CH3 ‐GBUT to CH3 ‐BIBUT conversion proceeds via a thermal pathway with a characterized transition state (TS). For all the three systems "on the fly" surface hopping molecular dynamics were performed.